Options contracts from an Islamic perspective - Eşref Devabe (Darulfunun Ilahiyat)
Option contracts are an essential financial derivatives tool as they have opened the way for investors to hedge against risks in an environment characterized by risk and uncertainty. Options also enable investors to speculate based on financial leverage. However, some view options contracts to have turned from being contracts that were initially a risk to contracts for hedging against risks. In reality, options are still associated with the same risk; they are nothing but gambling tools for trading in risks, as they are sold and bought by transferring them to those who accept the risk transfer. In light of many Arab countries’ tendency toward implementing options contracts in their financial markets, especially in Gulf countries, and their attempts to provide a legal character to their transactions, this study aims to determine the ruling regarding these contracts from the perspective of Islamic economics. The study relies on inductive and deductive approaches and deals with the concept of options, their origin and development, types, characteristics, and Islam’s perspective toward them. The study has concluded that option contracts are not permissible and that Islamic economic alternatives have been developed to hedge against price-change related risks by selling the deposit and the binding promise while not putting them up for trade.